Cover Feature: Defect Control in the Synthesis of 2 D MoS2 Nanosheets: Polysulfide Trapping in Composite Sulfur Cathodes for Li–S Batteries (ChemSusChem 6/2020). Issue 6 (12th March 2020) - Abraham, Alyson; Wang, Lei; Quilty, Calvin D.; Lutz, Diana M.; McCarthy, Alison H.; Tang, Christopher R.; Dunkin, Mikaela R.; Housel, Lisa M.; Takeuchi, Esther S.; Marschilok, Amy C.; Takeuchi, Kenneth J.
Abstract : The Cover Feature shows the synthesis and thorough characterization of hydrothermally prepared MoS2 nanosheets that vary in layer number, morphology, lateral size, and defect content. The materials were incorporated into composite sulfur‐based cathodes and studied in Li–S batteries with environmentally benign ether‐based electrolytes. Through directed synthesis of the MoS2 additive, the relationship between synthetically induced defects in 2 D MoS2 materials and resultant electrochemistry was elucidated. More information can be found in the Full Paper by A. Abraham et al. on page 1517 in Issue 6, 2020 (DOI: 10.1002/cssc.201903028 ).